2018
DOI: 10.1016/j.ihj.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of diets rich in almonds and walnuts on endothelial function

Abstract: Both walnut and almond diets improved FMD and sVCAM and there was no significant difference in physiological and biochemical markers between the two diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Most past studies that have measured blood pressure have reported no change with dietary walnuts [ 16 , 28 ]. However, several studies have reported improved endothelial function in association with walnuts, with increased flow-mediated dilation in overweight volunteers [ 29 ], in hyperlipidemic patients [ 30 ], and improved endothelial function in association with walnuts was confirmed in a systematic review [ 31 ]. There is evidence that endothelial and vascular function may be improved through increased production of nitric oxide from its precursor arginine, and through inhibition of endothelin-1 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most past studies that have measured blood pressure have reported no change with dietary walnuts [ 16 , 28 ]. However, several studies have reported improved endothelial function in association with walnuts, with increased flow-mediated dilation in overweight volunteers [ 29 ], in hyperlipidemic patients [ 30 ], and improved endothelial function in association with walnuts was confirmed in a systematic review [ 31 ]. There is evidence that endothelial and vascular function may be improved through increased production of nitric oxide from its precursor arginine, and through inhibition of endothelin-1 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that endothelial and vascular function may be improved through increased production of nitric oxide from its precursor arginine, and through inhibition of endothelin-1 [ 27 ]. In addition, walnuts have been associated with reduced circulating adhesion molecules, such as vascular cell adhesion molecule-1 (VCAM-1) and E-Selectin [ 29 , 32 ], as well as reduced circulating inflammatory markers in humans and mice [ 18 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommended that 84 g of walnut on a daily basis for four weeks has a potential to decrease serum levels of total cholesterol by 12% [54]. The beneficial effect of walnut consumption in reducing the risk of CVD is not limited to reducing blood cholesterol level only but also attributed to the lowering LDL-C, vascular inflammation, improving endothelial dysfunction and enhancing antioxidant activity [55][56][57]. The cholesterol lowering effect of walnut could be due to the presence of phytosterols in it.…”
Section: Walnut and Cardiovascular Diseasementioning
confidence: 99%
“…For example, oral intake of 2 g of n-3 PUFAs per day for 12 weeks significantly improved FMD of brachial artery and pulse wave velocity in adults with metabolic syndrome (Tousoulis et al, 2014). A recent cross-over study in overweight individuals reported that a walnut-rich diet (23.1% energy from n-3 PUFAs) compared to an almond-rich diet significantly improved FMD of brachial artery and decreased soluble vascular cell adhesion molecule level (Bhardwaj et al, 2018). Furthermore, increased serum DHA level was a positive contributor to an increased FMD of brachial artery in 160 consecutive Japanese patients with coronary artery disease (Yagi et al, 2015).…”
Section: The Effect Of N-3 Pufas and Exercise On Vascular Function Inmentioning
confidence: 99%